2017
DOI: 10.3892/ol.2017.6414
|View full text |Cite
|
Sign up to set email alerts
|

Role of depth of response and MTHFR genotype as predictors of fluorouracil rechallenge therapy for refractory metastatic colorectal cancer

Abstract: Abstract. There is limited data on the clinical and biological parameters that enable the prediction of the benefits derived from additional chemotherapy after disease progression compared with standard chemotherapy in patients with metastatic colorectal cancer (mCRC). The present study evaluated the role of tumor response as a clinical parameter and single nucleotide polymorphisms (SNPs) as a biomarker to predict the benefit of additional 5-fluorouracil (5-FU) rechallenge chemotherapy in patients with refract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…It indicated that patients whose DpR ≥45% was correlated with longer PFS (median 16.4 vs. 8.1 months for DpR <45%, P=0.006) and OS (median 58.6 vs. 30.9 months for DpR <45%, P=0.041). Similar results were also obtained in Kim et al ’s ( 28 ) retrospective study of patients receiving chemotherapy alone. PFS, OS, and PPS of patients with DpR ≥60% were significantly improved.…”
Section: Methodssupporting
confidence: 88%
“…It indicated that patients whose DpR ≥45% was correlated with longer PFS (median 16.4 vs. 8.1 months for DpR <45%, P=0.006) and OS (median 58.6 vs. 30.9 months for DpR <45%, P=0.041). Similar results were also obtained in Kim et al ’s ( 28 ) retrospective study of patients receiving chemotherapy alone. PFS, OS, and PPS of patients with DpR ≥60% were significantly improved.…”
Section: Methodssupporting
confidence: 88%
“…Two common polymorphism variants with the outcome of MTHFR enzymatic deficiency have been identified, namely, the rs1801133 (C677T) and rs1801131 (A1298C) [ 269 ]. Positive correlation between MTHFR polymorphisms and colon cancer patient’s response to 5-FU treatment is often reported involving variant A1298C with C677T seeing 5-FU benefits only exclusively in refractory cases [ 239 , 270 , 271 ]. Interestingly, in vitro studies have implicated both polymorphisms in the development of 5-FU resistance in colon cancer cells [ 240 ].…”
Section: Mechanism Of Resistance By Key 5-fluorouracil Enzymesmentioning
confidence: 99%
“…In a recent study conducted in two cohorts of stage II/III of CRC patients treated with adjuvant fluoropyrimidine chemotherapy, the MTHFR 1298CC genotype carriers underwent worsened disease free survival and overall survival in both cohorts [ 51 ]. Similarly, an even more recent study of 242 Korean patients with mCRC showed that the presence of a C677CC genotype was associated with a good prognosis in multivariate analysis [ 52 ]. On the basis also of the significant ethnic differences in the C677T and A1298C genotypes frequency, larger studies including different populations are needed to determine the role of these polymorphisms in response to fluoropyrimidines [ 53 ].…”
Section: Fluoropyrimidinesmentioning
confidence: 99%